Short communication: System of wheat intensification in farmers’ field of Sindhuli, Nepal - Adhikari, D (Agronomy Journal of Nepal, 2013)
Food requirement is increasing day by day whereas production of food is not sufficient or decreasing due to various factors. In Nepal, wheat is third major cereal crop after rice and maize both in area and production, and can be grown all over the country successfully during winter season. A study was conducted during 2011/12 to determine the performance of System of Wheat Intensification (SWI) at farmers’ field of Bhimasthan, Sindhuli, Nepal. Germinated seed of wheat variety Bhirkuti was shown on 6th Dec 2011 in the spacing 20x20 cm. Average tiller number and number of effective tillers were 25 and 21 respectively. Average plant height was 61.5 cm. at 65 Days after Sowing. The results of this study showed that plant height, numbers of tillers/ hill, number of productive tillers, panicle length, and production were found higher in SWI method. Yield of wheat variety (Bhirkuti) was found 2.6, 2.4 and 2.3 kg/4 m2 in SWI, Line sown and broadcast practices, respectively. Agronomy Journal of Nepal (Agron JN) Vol. 3. 2013, Page 168-171 DOI: http://dx.doi.org/10.3126/ajn.v3i0.9019